A census of compact sources at 162 MHz: First data release from the MWA Phase II IPS Survey. (23rd December 2022) - Morgan, J. S.; Chhetri, R.; Ekers, R.
Abstract: We present a catalogue of over 7000 sources from the GLEAM survey which have significant structure on sub-arcsecond scales at 162 MHz. The compact nature of these sources was detected and quantified via their Interplanetary Scintillation (IPS) signature, measured in interferometric images from the Murchison Widefield Array. The advantage of this approach is that all sufficiently compact sources across the survey area are included down to a well-defined flux density limit. The survey is based on 250× 10-min observations, and the area covered is somewhat irregular, but the area within 1 h<RA<11 h ; -10^°<Decl.<+20^° is covered entirely, and over 85% of this area has a detection limit for compact structure below 0.2 Jy. 7839 sources clearly showing IPS were detected ( >5σ confidence), with a further 5550 tentative ( >2σ confidence) detections. Normalised Scintillation Indices (NSI; a measure of the fraction of flux density coming from a compact component) are reported for these sources. Robust and informative upper limits on the NSI are reported for a further 31081 sources. This represents the largest survey of compact sources at radio frequencies ever undertaken.